Complex CDKL5 translational regulation and its potential role in CDKL5 deficiency disorder - Ruggiero, Valeria; Fagioli, Claudio; de Pretis, Stefano; Di Carlo, Valerio; Landsberger, Nicoletta; Zacchetti, Daniele (Frontiers in Cellular Neuroscience, 2023)
CDKL5 is a kinase with relevant functions in correct neuronal development and in the shaping of synapses. A decrease in its expression or activity leads to a severe neurodevelopmental condition known as CDKL5 Deficiency Disorder (CDD). CDD arises from CDKL5 mutations that lie in the coding region of the gene. However, the identification of a SNP in the CDKL5 5'UTR in a patient with symptoms consistent with CDD, together with the complexity of the CDKL5 transcript leader, points toward a relevant translational regulation of CDKL5 expression with important consequences in physiological processes, as well as in the pathogenesis of CDD. We performed a bioinformatics and molecular analysis of the 5'UTR of CDKL5 to identify translational regulatory features. We propose an important role for structural cis-acting elements, with the involvement of the eukaryotic translational initiation factor eIF4B. By evaluating both cap-dependent and capindependent translation initiation, we suggest the presence of an IRES supporting the translation of CDKL5 mRNA and propose a pathogenic effect of the C>T -189 SNP in decreasing the translation of the downstream protein.